Novel chemometric-driven greenness assessed spectroscopical method development and forced degradation study of sitagliptin phosphate in its bulk drug and ophthalmic formulation - Debashis Mishra; Himansu Bhusan Samal; Diptimayee Jena; Kirtimaya Mishra (Creative Pharma Assent, 2026)
Background: Sitagliptin phosphate (SIT), an antidiabetic drug, requires reliable analytical methods for routine quality control and stability assessment. UV-visible spectrophotometry offers a simple and economical approach; however, method robustness and stability-indicating capability must be ensured using systematic development strategies such as Quality by Design (QbD). The objective of this work is to develop and validate a rapid, simple, economical, accurate, and precise UV-visible spectrophotometric method with a stability-indicating capability for the analysis of SIT in bulk drug and ophthalmic formulation. Methodology: Method development was performed using a QbD approach in a quality control laboratory with a UV-visible spectrophotometer and 1 cm quartz cells. Various solvents (phosphate buffer, ethanol, acetonitrile, methanol, and water) were evaluated, with water selected due to superior solubility and spectral characteristics. SIT showed maximum absorbance at 265-267 nm. Forced degradation studies (acidic, basic, oxidative, thermal, and photolytic) were conducted. Validation was performed as per ICH Q2 (R1) guidelines. Results and Discussion: The developed method exhibited excellent linearity (R² ≥ 0.998), accuracy (99-101% recovery), and precision (%RSD ≤ 2%). Recovery ranged from 98.68% to 99.46%. The method was robust and successfully indicated stability under stress conditions. The application of QbD ensured systematic optimization and robustness. Water proved to be an ideal solvent, enhancing method simplicity and cost-effectiveness. The method effectively distinguished SIT from degradation products, confirming its stability-indicating nature. Conclusion: A validated, reliable, and economical UV-visible spectrophotometric method was successfully developed for SIT analysis, suitable for routine quality control and stability studies in bulk drug and ophthalmic formulations.